Gaps in Understanding the Experiences of Homecare Workers Providing Care for People with Dementia up to the End of Life: A Systematic Review. (April 2019) - D'Astous, Valerie; Abrams, Ruth; Vandrevala, Tushna; Samsi, Kritika; Manthorpe, Jill
This systematic review of the literature explores the perspectives and experiences of homecare workers providing care for people with dementia living at home up to the end of life. A search of major English language databases in 2016 identified 378 studies on the topic, of which 12 met the inclusion criteria. No empirical research was identified that specifically addressed the research question. However, synthesis of the findings from the broader literature revealed three overarching themes: value of job role, emotional labour and poor information and communication. The role of homecare workers supporting a person with dementia up to the end of life remains under-researched, with unmet needs for informational, technical and emotional support reported. The effective components of training and support are yet to be identified.